2019
DOI: 10.1186/s12913-019-4750-5
|View full text |Cite
|
Sign up to set email alerts
|

Working well: strategies to strengthen the workforce of the Indigenous primary healthcare sector

Abstract: BackgroundThe capacity of the Indigenous primary healthcare (PHC) sector to continue playing a crucial role in meeting the health needs of Aboriginal and Torres Strait Islander Australians is in large part reliant on the skills, motivation and experience of its workforce. While exhibiting many workforce strengths, the sector faces significant challenges in building and maintaining a strong and stable workforce. Drawing on data from one Aboriginal Community Controlled Health Service (ACCHS), this study reports … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 27 publications
(64 reference statements)
2
38
0
Order By: Relevance
“…AHWs initiated interagency communication, facilitated communication, were often the conduit between other healthcare workers and patients, transported patients to and from appointments and provided one-on-one case management. This is consistent with previous research that reported ACCHOs are already implementing many important workforce development strategies that are having a positive impact on health service utilization and patient outcomes [ 30 ]. Our findings highlight that these approaches should be tailored to local needs and contexts.…”
Section: Discussionsupporting
confidence: 93%
“…AHWs initiated interagency communication, facilitated communication, were often the conduit between other healthcare workers and patients, transported patients to and from appointments and provided one-on-one case management. This is consistent with previous research that reported ACCHOs are already implementing many important workforce development strategies that are having a positive impact on health service utilization and patient outcomes [ 30 ]. Our findings highlight that these approaches should be tailored to local needs and contexts.…”
Section: Discussionsupporting
confidence: 93%
“…Through our case studies with cancer services around Australia, we observed that it "starts from the top"; if the commitment to Indigenous health and workforce is dependent on just one or two dedicated employees then efforts can diminish over time as supportive staff leave or get burnt out. This reflects findings by other studies, including Jongen et al [41] who found that strong leadership was essential for a strong and stable Indigenous primary health care workforce and the Mason Review of Health Workforce Programs, which states "Aboriginal and Torres Strait Islander leadership is recognised internationally as a key factor in the development and sustainability of programs aimed at increasing Aboriginal and Torres Strait Islander workforce capacity, and influencing the non-Aboriginal and Torres Strait Islander health workforce to provide culturally safe and appropriate services" [42].…”
Section: Discussionsupporting
confidence: 91%
“…Strengths of the PHC services identified by staff and community provide evidence of the immutable interconnection between culture, community and the delivery of quality care and builds on what we know about two way learning and community driving health [ 11 , 23 ]. Critical to a “strong” PHC service response to quality improvement was an integrated Aboriginal and Torres Strait Islander workforce that (teamwork) that were supported (through appropriate training, QI systems and leadership) and valued in their provision of quality care to the community [ 10 , 35 ]. These factors, including the esteem in which Aboriginal staff are held and the valuing of their input have also been identified as critical in high performing tertiary health services [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with mechanisms to facilitate community engagement, these enable perseverance with participation in QI [ 6 , 8 ]. In contrast, some services show limited improvement (or sometimes none), due to a range of interwoven implementation, resourcing and community contextual factors, often the inverse of those underlying high performance [ 9 , 10 ]. To achieve Aboriginal and Torres Strait Islander population health impact, we need to understand how to strengthen the quality of care in PHC on a broad scale and broaden our discourse on quality as defined by the communities we serve [ 11 ].…”
Section: Introductionmentioning
confidence: 99%